ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU CORPORATE INTERNET REPORTING PADA PERUSAHAAN-PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - WIDARYANTI, Ibu (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2011)
This study seek to examined factors that affect the timeliness of corporate internet reporting (CIR) in listed companies on the Indonesian Stock Exchange. Key factors used firm characteristics (firm size, type of bussiness, profitability, leverage, liquidity, issuance of stock) and corporate governance variables (public ownership structure, proportion of supervisory board and supervisory board size). Population of this study was Indonesian Listed Company in 2008 at Indonesian Stock Exchange .The sample was 195 firms Based on purposive sampling technique. Multiple regression analysis used to test the hypothesis. The regression analysis found that a significant relationship between the timeliness of CIR and firm size. However, others variable like type of bussiness, profitability, leverage, liquidity, stock issues, public ownership structure, proportion of supervisory board and supervisory board size was not significant relationship with timeliness of CIR.. This results indicated that firms typically in big size se modisclore timely information on their web sites.